2015
DOI: 10.1007/s00421-015-3100-5
|View full text |Cite
|
Sign up to set email alerts
|

The electromyographic threshold in boys and men

Abstract: The boys' higher EMGTh suggests delayed and hence lesser utilization of type-II MUs in progressive exercise, compared with men. The boys-men EMGTh differences were of similar magnitude as those shown for LaTh and VeTh, further suggesting a common underlying factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
4
16
0
1
Order By: Relevance
“…In this regard, it is known that the electromyographic (EMG) threshold may be detected during incremental exercise, and the EMG threshold is defined as a nonlinear increase or upward inflection of EMG signals with increase in exercise intensity (Lucía et al ., ; Osawa et al ., ; Crozara et al ., ; Pitt et al ., ). It has been reported that the EMG threshold for the m. vastus lateralis was identified in 90%–100% of the subjects in cycling, which has a constant movement pattern (Lucía et al ., ; Osawa et al ., ; Pitt et al ., ), while the corresponding value in treadmill running was 54% (Crozara et al ., ). Therefore, we suspect that the absence of the point of accelerated decrease in Δ[Oxy‐Hb − Deoxy‐Hb] in some participants in this study might be attributable to individual differences in movement pattern while running.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard, it is known that the electromyographic (EMG) threshold may be detected during incremental exercise, and the EMG threshold is defined as a nonlinear increase or upward inflection of EMG signals with increase in exercise intensity (Lucía et al ., ; Osawa et al ., ; Crozara et al ., ; Pitt et al ., ). It has been reported that the EMG threshold for the m. vastus lateralis was identified in 90%–100% of the subjects in cycling, which has a constant movement pattern (Lucía et al ., ; Osawa et al ., ; Pitt et al ., ), while the corresponding value in treadmill running was 54% (Crozara et al ., ). Therefore, we suspect that the absence of the point of accelerated decrease in Δ[Oxy‐Hb − Deoxy‐Hb] in some participants in this study might be attributable to individual differences in movement pattern while running.…”
Section: Discussionmentioning
confidence: 97%
“…In Japan, the 20mSRT is one of the physical fitness tests adopted by the Ministry of Education, Culture, Sports, Science and Technology and is conducted nationwide. It was demonstrated that children have unique physiological responses to exercise (Takagi et al ., ; Armstrong et al ., ; Pitt et al ., ) and that muscle oxygenation response during treadmill running in children is different from that in adults (Takagi et al ., ). Therefore, it is necessary to clarify the characteristics of muscle oxygenation profiles during the 20mSRT in children and its relationship with 20mSRT performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that PRE youth rely more on aerobic metabolism during submaximal exercise than POST youth due to their underdeveloped anaerobic system (Boisseau & Delamarche, 2000). These maturity‐related differences in the metabolic response to exercise may be observed in anaerobic, or fatigue, thresholds, which have been previously demonstrated to occur at lower absolute intensities in children when compared to adults (Anderson & Mahon, 2007; Klentrou, Nishio, Plyley, & University, 2006; Pitt et al., 2015). Furthermore, maturity status has been shown to influence the onset of systemic pulmonary and localized muscular fatigue thresholds, with fatigue thresholds occurring at higher relative intensities in PRE when compared to POST (Beyer et al., 2019).…”
Section: Introductionmentioning
confidence: 94%
“…After the key study of Lucía et al, there continues to be a discrepancy in the number and interpretation of EMG breakpoints identified during incremental tests [30,31]. Remarkably, automatic methods used by most authors for EMG-threshold detection had the limitation that only one EMG breakpoint could be possibly identified [8,9,32,33]. Essentially, these methods are based on calculating all the two-segment regressions for the data, and then choosing the two-segment regression with the least residual sum of squares, thus yielding a single intersection point.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%